The Influence of Interest in Learning English on Learning Outcomes in Narrative Texts - Yosi Andana; Afiyah Haura Salsabilla; Syarifah Widya Ulfa (Universitas Muhammadiyah Enrekang, 2023)
The aim of this research is to determine the influence of learning interest on learning activities regarding narrative text material. The research was carried out at the MA Islamic Center Medan, class XA with a total of 26 students. The research was carried out in semester 2 (Even) of the 2022/2023 academic year in October and November 2023. The classroom action research design was planned to consist of two cycles. In the first cycle, class In the second cycle of activities, class Data collection for Classroom Action Research (PTK) is as follows, (1) observation and (2) questionnaire on student learning activities. The conclusion of the research is that the peer tutoring learning method is used as a reference for implementing the independent curriculum (IKM) in schools because it really involves students and can increase student learning activities in PBM.